PELATIHAN KEWIRAUSAHAAN PEREMPUAN MEMBERDAYAAN MASYARAKAT PASCA BENCANA ALAM - Agus Winarti (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2019)
Training is a process that aims to improve the skills and abilities beyond the prevailing education system, to a person, group or community. The training program is expected to revive the economy after the Merapi disaster victims. Problems faced by the community is the loss of livelihood as a farmer who is the foundation of life for their families devastated swept lava and hot clouds (wedus trash) trim. The purpose of this training is for the empowerment of the people who lost their livelihoods from farming to switch professions as entrepreneurial as the target is an adult female. In the process of development is necessary that adult women are empowered to the fullest, so what is the purpose in meeting the needs of family life can be fulfilled in line with expectations. women with entrepreneurial training can improve the economics of the family. The method used to approach the research and development (R & D), engineering data collection is done through in-depth interviews, questionnaires, observation, and documentation. The results showed the presence of the training have the knowledge, skills, behaviors, and attitudes to entrepreneurship in everyday life to be able to support the family economy.